Serum atrial natriuretic peptide: a suspected biomarker of breast cancer - Houssen, Maha E.; Ghazy, Hayam F.; Farag, Kamel; El-Hussiny, Mona Abo Bakr; Ghaffar, Mohamed A. El; Alsayed, Sahar Alsayed Mohamed; Farouk, Omar (Contemporary Oncology/Współczesna Onkologia, 2017)
Aim of the study : To assess serum levels of ANP in breast cancer female patients and its relationship to metastasis and some clinical parameters among those patients. Material and methods : One hundred breast cancer patients with and without metastasis along with 20 healthy closely matched controls, were enrolled in the present cross sectional study. Background: To assess the serum levels of atrial natriuretic peptide in breast cancer Serum levels of ANP were assessed using ELISA. Results : Mean serum levels of ANP breast cancer patients (13.9 ±10.1 ng/ml) were significantly elevated compared to healthy control group (2.2 ±1.3 ng/ml) (p < 0.001). The metastatic breast cancer patients showed significant elevated ANP levels (17.1 ±8.9 ng/ml) compared to non-metastatic group (6.4 ±8.8 ng/ml) p < 0.001. Within the metastatic group significant difference was detected between de novo metastatic, under follow-up, under hormonal control and locally advanced group (p = 0.007). Conclusions : This study showed significant elevated levels of ANP in the serum of metastatic breast cancer patients compared to non-metastatic patients. Within the metastatic group the lowest levels were detected in metastatic breast Cancer under hormonal treatment either tamoxifen or aromatase inhibitor.